Laser illumination-induced dramatic catalytic activity change on Au nanospheres - Ye, Zhongju (Royal Society of Chemistry, 2019)

(untitled) (Chem Sci)
Understanding morphology dependent catalytic kinetics from a single nanoparticle plays a significant role in the development of robust nano-catalysts with high efficiency. Unfortunately, detailed knowledge of the morphology dependent catalytic properties of single nanoparticles after shape transitions is lacking. In this work, the distinct catalytic properties of a single gold nanoparticle (GNP) after symmetry breaking were disclosed at the single-particle level for the first time. The morphology of the spherical GNP was elongated into a rod shape (i.e., gold nanorod, GNR) with a tightly focused Gaussian laser beam based on the photothermal effect. By using the fluorogenic oxidation reaction (i.e., amplex red to resorufin) as a model reaction, noticeable variation in catalytic efficiency after the shape modulation process was found at the single-particle level. The GNP displays noticeably higher catalytic efficiency which might be ascribed to the heterogeneous lattice structure on the particle surface as confirmed by transmission electron microscopy (TEM) characterization. Rearrangement of surface atoms after shape modulation normally generates a more ordered crystal structure, resulting in a lower surface energy for catalytic reaction. However, both of these nanoparticles still exhibit dynamic activity fluctuation in a temporal dependent route, indicating a distinct spontaneous dynamic surface restructuring process. These kinetic evidences might facilitate the development nanoparticle-based heterogeneous catalysts, particularly based on the morphology effect.